Impact of COVID-19 on Oil and Gas Sector in Nigeria: A Condition for Diversification of Economic Resources - Yusuff Jelili Amuda (Emerging Science Journal, 2023)
A plethora number of literature advocates for economic diversification in Nigeria in order to address its socio-economic challenges. The advent of the COVID-19 pandemic has exemplified this viewpoint even further, as it has had a severe impact on many parts of the Nigerian economy while the federal government scrambles for revenue to fulfill national expenses. However, observation reveals that little attention is paid to the influence of COVID-19 on the oil and gas sector, despite the necessity to diversify economic resources for human capital development. The purpose of this research is to investigate the influence of COVID-19 on the Nigerian oil and gas sector. Problems are recognized and solutions are proposed through the textual analysis of literature. According to the research, COVID-19 has a negative influence on the oil and gas business in Nigeria due to Nigeria's overreliance on oil resources as a key source of national revenue, among other issues. As a result, the study emphasized the need for and importance of diversifying the nation's economic resources by focusing more attention on sectors such as SMEs that are aided with protection and promotion, as well as the agricultural sector, which incorporates technology and scientific input as a driving force for improvement. If adopted, diversification will address numerous difficulties such as poverty, which affects the majority of inhabitants, unemployment, mounting foreign debt, and the massive importation of products and services into the country due to a lack of economic diversification. According to the report, the Nigerian government should invest extensively in small and medium-sized firms (SMEs) and agricultural investment in order to overcome the economic challenges caused by COVID-19's detrimental influence on the economy. Doi: 10.28991/ESJ-2023-SPER-019 Full Text: PDF